Bionic fluorescence enhanced substrate for sensing and detecting mercury ions and preparation method of bionic fluorescence enhanced substrate

By modifying precious metal nanoparticles and quantum dots on the substrate, and combining silicone molecules and functionalized molecules to form a bionic fluorescence enhancement substrate, the problems of insufficient sensitivity and expensive equipment in the prior art are solved, and high sensitivity, rapid response and inexpensive mercury ion detection are achieved.

CN119827465APending Publication Date: 2025-04-15WUXI ZHENXIN TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411958151.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The prior art has problems such as insufficient sensitivity in mercury ion detection, expensive equipment, complex sample processing, long detection time and susceptible to environmental interference, making it difficult to meet the needs of fast, sensitive and inexpensive detection.

Method used

A biomimetic fluorescence enhancement substrate is used to modify precious metal nanoparticles on the substrate, deposit non-conductive films and siloxane molecules, and finally modify quantum dots and functionalized molecules to form a composite substrate that can specifically detect mercury ions.

Benefits of technology

It realizes high sensitivity detection of mercury ions, with the detection limit reaching 10-11~10-13mol/L, and has the characteristics of rapid response, inexpensiveness and wide linear range to meet practical application needs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119827465A_ABST
    Figure CN119827465A_ABST
Patent Text Reader

Abstract

The invention discloses a bionic fluorescence enhanced substrate for sensing and detecting mercury ions and a preparation method of the bionic fluorescence enhanced substrate, and belongs to the technical field of photoelectric sensing devices. The bionic fluorescence enhanced substrate comprises a substrate; the noble metal particles are positioned on the surface of the substrate; an anti-fluorescence quenching protective layer on the noble metal particles; wherein the substrate, the noble metal particles and the anti-fluorescence quenching layer have a fluorescence enhancement effect; the specific mercury ion sensing detection layer is positioned on the surface of the anti-fluorescence quenching protection layer; the specific mercury ion sensing detection layer comprises fluorescent quantum dots; and the mercury ion specific recognition layer is bonded on the surface of the fluorescent quantum dot. The detection limit of the substrate on mercury ions is 10 <-11 > to 10 <-13 > mol / L.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of photoelectric sensor devices, and in particular relates to a bionic fluorescence enhancement substrate for mercury ion sensing and detection and a preparation method thereof. Background Art

[0002] Many heavy metal ions are highly toxic and non-biodegradable. For example, the content of mercury ions in surface water has doubled since the Industrial Revolution. They are converted into methylmercury by microorganisms and enter the human body through the food chain, which has serious harmful effects on human health, especially the central nervous system. Therefore, it is urgent to establish a method that can quickly, sensitively and traceably detect mercury ions. However, traditional mercury ion detection methods include atomic absorption spectroscopy, inductively coupled plasma atomic emission spectroscopy, inductively coupled plasma mass spectrometry, ultraviolet visible spectroscopy and electrochemical sensors, which can detect mercury ions sensitively and selectively; however, the above detection methods have certain defects, such as atomic absorption spectroscopy, inductively coupled plasma mass spectrometry and inductively coupled plasma atomic emission spectroscopy are highly sensitive, but require large and expensive instruments, and the sample preparation method is relatively complicated, making it difficult to promote and popularize; high performance liquid chromatography detection means are mild, samples can be recovered, and the detection limit is relatively low, but the detection time is relatively long; ultraviolet visible spectroscopy detection means are relatively simple, the detection instrument is relatively cheap, and has certain specific detection, but it is easily disturbed by the external environment and the detection limit is relatively low, which cannot meet the use; and electrochemical sensors are limited in actual use due to their complex three-phase electrode system and susceptibility to complex environmental interference. Therefore, it is urgent to develop a detection method that can respond reliably and quickly, has high sensitivity, is cheap, and has a relatively wide linear range. The fluorescence sensing detection method is favored due to its advantages such as wide linear range, high sensitivity, good selectivity, relatively cheap detection instruments and simple sample processing, and is expected to be widely used.

[0003] Fluorescent substances have different optical properties before and after detecting analytes. Compared with detection technologies such as inductively coupled plasma mass spectrometry, atomic emission spectroscopy, and high performance liquid chromatography, they have different photophysical mechanisms, which makes fluorescent sensors superior to other detection methods in terms of detection sensitivity, linearity, and detection methods. Quantum dots (QDs) have become an ideal fluorescent probe due to their high fluorescence quantum efficiency, adjustable emission spectrum, wide excitation spectrum and narrow excitation spectrum, good photochemical stability, good biocompatibility, and easy modification. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a method for preparing a bionic fluorescence enhanced substrate for mercury ion sensing detection, comprising:

[0005] Constructing a substrate, wherein the substrate is one or more of single crystal silicon, polycrystalline silicon, quartz, glass, fluorine-doped tin dioxide conductive glass, indium tin oxide conductive glass, carbon cloth, paper, cellulose film, stainless steel, metal nickel, metal copper, metal titanium, titanium oxide, metal aluminum, aluminum oxide, indium phosphide, silicon carbide, silicon nitride, diamond, sapphire, gallium arsenide, polydimethylsiloxane, polyethylene terephthalate, polymethyl methacrylate, polyethylene, and polyvinylidene fluoride; the surface of the substrate has a light trapping structure, and the light trapping structure is one or more of a pyramid shape, a column shape, a rod shape, a tube shape, a nanowire shape, an inverted pyramid shape, a nanosheet shape, a bowl shape, and a porous shape;

[0006] Next, the prepared substrate with light trapping ability is modified with precious metal nanoparticles having bionic dendritic, flower-like, sea urchin-like and other morphologies by one or more methods selected from chemical deposition technology, electrodeposition technology, electrical displacement reaction technology and photoreduction technology to obtain a bionic fluorescence enhancement substrate with fluorescence enhancement ability; the precious metal nanoparticles are one or more selected from silver, gold, copper, platinum and alloys thereof;

[0007] Next, a non-conductive film is deposited on the noble metal nanoparticles, and the non-conductive film plays a role in preventing fluorescence quenching. The non-conductive film is one or more of aluminum oxide, SiO2, PMMA, polyvinyl acetate polymers, polyacrylamide polymers, polyethylene glycol, polyallylamine, polystyrene polymers, polyether polymers, polyvinyl alcohol, polysiloxane, polyurethane, glass, polydopamine, zirconium oxide, hydroxyapatite, and aluminosilicate;

[0008] Next, the prepared fluorescence enhancement substrate is modified with siloxane molecules, wherein the siloxane molecules need to contain one or more functional groups of amino, carboxyl, and pyridine groups, including but not limited to one or more of 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, dimethylaminotrimethylsilane, 3-carboxypropyltrimethoxysilane, 4-anilinotriethoxysilane, and N-(3-trimethoxysilylpropyl)pyrrole;

[0009] Next, quantum dots are modified on the fluorescence enhancement substrate prepared above, including but not limited to one or more of ZnO quantum dots, MgO quantum dots, CuO quantum dots, g-C3N4 quantum dots, CdS quantum dots, MoS2 quantum dots, zinc sulfide quantum dots, zinc selenide quantum dots, cadmium selenide quantum dots, lead sulfide quantum dots, lead selenide quantum dots, graphene quantum dots, and carbon quantum dots;

[0010] Finally, the substrate obtained above is subjected to functionalization treatment to specifically detect mercury ions. The functionalized molecules, i.e., specific recognition molecules, contain thiol and amino functional groups, including but not limited to one or more of thioimidazole, thioglycolic acid, thiopropionic acid, amino acid molecules, triethanolamine, glutathione, mercaptosuccinic acid, and cysteine; the amino group of the specific recognition molecule is interconnected with the quantum dot, and the thiol group at the other end is used to detect Hg 2+ , due to Hg 2+ The specific binding to thiol groups makes Hg 2+ Connected to quantum dots, quenching their fluorescence, thus detecting Hg 2+ .

[0011] The present invention also provides a bionic fluorescence enhancement substrate for mercury ion sensing and detection prepared by the method described above.

[0012] Beneficial effects of the present invention:

[0013] The detection limit of mercury ions by the bionic fluorescence enhancement substrate prepared by the present invention is 10 -11 ~10 -13 mol / L. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 The figure is a schematic diagram of the preparation process of the bionic fluorescence enhancement substrate for mercury ion sensing detection according to the present invention. DETAILED DESCRIPTION

[0015] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0016] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0017] Unless otherwise specified, the raw materials used in the examples were purchased commercially.

[0018] Example 1

[0019] a. Preparation of silicon cone substrate (P / Si):

[0020] The silicon wafer was treated with acetone, chloroform, ethanol and deionized water in sequence under ultrasonic conditions for 5 minutes; then, the sample was placed in a 0.1 mol / L potassium hydroxide aqueous solution and reacted at 80°C for 30 minutes to obtain a silicon cone (P / Si) sample with light trapping ability; then, the sample was taken out, rinsed with deionized water, and blown dry for later use;

[0021] b. Preparation of biomimetic fluorescence enhanced substrate (Ag ND-P / Si):

[0022] The sample was placed in a mixed solution of silver nitrate (AgNO3) and hydrofluoric acid (HF) with concentrations of 0.01 mol / L and 2.0 mol / L respectively for 11 min to deposit silver nanocrystals Ag ND, thereby obtaining a bionic fluorescence enhanced substrate Ag ND-P / Si.

[0023] c. Preparation of anti-fluorescence quenching substrate (SiO2@Ag ND-P / Si):

[0024] 40.0mL of ethanol, 15.0mL of ammonia water and 3.0mL of tetraethyl orthosilicate were reacted at a constant temperature for 20min; then, 0.3mL of ammonia water was added to the above reaction solution, and the reaction was stirred for 2h to obtain SiO2 sol; then, 20μL of the above prepared SiO2 sol was diluted to different concentrations and added dropwise to the silver nano-dendritic structure; finally, the sample was placed in a muffle furnace, the heating rate was controlled at 5℃ / min, the temperature was raised to 70℃, cured for 1h, and then the temperature was raised to 150℃, and calcined at 150℃ for 1h to obtain SiO2@AgND-P / Si structure;

[0025] d. Preparation of ZnO quantum dots modified fluorescence enhancement substrate (ZnO QDs@SiO2@Ag ND-P / Si):

[0026] First, ZnO quantum dots were prepared: 20 mL of 0.4 mol / L LiOH·H2O was added to 40 mL of 0.2 mol / L ZnAc2·2H2O ethanol solution, and the mixture was stirred at 20°C for 20 min to obtain a ZnO quantum dot ethanol solution; then, 60 mL of the ZnO quantum dot ethanol solution was added to 120 mL of n-hexane to produce a white granular precipitate, which was allowed to stand for 2 h; finally, the mixture was centrifuged for 10 min (2000 r / min), the supernatant was removed, and 20 mL of anhydrous ethanol was added to dissolve the precipitate to obtain a clear and transparent ZnO sol;

[0027] At the same time, use a pipette to transfer 10 μL of 3-aminopropyltriethoxysilane and dissolve it in 50 mL of xylene solution, mix well and set aside;

[0028] Then, the prepared SiO2@Ag ND-P / Si composite substrate was immersed in a xylene mixture of 3-aminopropyltriethoxysilane for 1 hour; then, the sample was immersed in the prepared ZnO QDs sol to obtain a ZnO QDs@SiO2@Ag ND-P / Si composite substrate, in which 3-aminopropyltriethoxysilane is a silane coupling agent, which can bond with the hydroxyl group on the surface of the SiO2 shell layer, and fix the ZnO QDs on the substrate surface through the coordination of the lone pair electrons of the amino group with the zinc vacant orbital of the zinc oxide quantum dots;

[0029] e. Functionalization of ZnO quantum dots modified fluorescence enhancement substrate (ZnO QDs@SiO2@Ag ND-P / Si):

[0030] The composite substrate (ZnO QDs@SiO2@Ag ND-P / Si) was immersed in an aqueous solution of 0.1 mol / L mercaptoimidazole for functionalization to prepare a surface that can specifically detect Hg 2+ composite substrate.

[0031] The prepared ZnO QDs@SiO2@Ag ND-P / Si substrate has good anti-reflection properties, and the presence of the silica shell can effectively prevent the non-radiative transition of the fluorescent substance ZnO QDs to the silver nanodendrites to cause quenching, making the composite structure have excellent fluorescence enhancement performance, with an enhancement factor of up to 15.96. This substrate has Hg 2+ The specific detection performance is 10 -13 mol / L.

[0032] Example 2

[0033] a. Preparation of silicon cone substrate (P / Si):

[0034] The silicon wafer was treated with acetone, chloroform, ethanol and deionized water under ultrasonic conditions for 5 minutes in sequence; then, the sample was placed in a 0.1 mol / L sodium hydroxide aqueous solution and reacted at 80°C for 50 minutes to obtain a silicon cone (P / Si) sample with light trapping ability; then, the sample was taken out, rinsed with deionized water, and blown dry for standby use.

[0035] b. Preparation of fluorescence enhancement substrate (Ag ND-P / Si):

[0036] The sample was placed in a mixed solution of silver nitrate (AgNO3) and hydrofluoric acid (HF) with concentrations of 0.01 mol / L and 1.8 mol / L respectively. After reacting for 11 minutes, silver nanocrystal dendrites Ag ND were deposited to obtain the bionic fluorescence enhanced substrate Ag ND-P / Si.

[0037] c. Preparation of anti-fluorescence quenching substrate (SiO2@Ag ND-P / Si):

[0038] 40.0mL of ethanol, 15.0mL of ammonia water and 3.0mL of tetraethyl orthosilicate were reacted at a constant temperature for 20min; then, 0.3mL of ammonia water was added to the above reaction solution, and the reaction was stirred for 2h to obtain SiO2 sol; then, 20μL of the above prepared SiO2 sol was added dropwise to the silver nano-dendrite structure, and finally, the sample was placed in a muffle furnace, the heating rate was controlled at 5℃ / min, the temperature was raised to 70℃, solidified for 1h, and then the temperature was raised to 150℃, and calcined at 150℃ for 1h to obtain SiO2@Ag ND-P / Si structure;

[0039] d. Preparation of MoS2 quantum dot modified fluorescence enhancement substrate (MoS2 QDs@SiO2@Ag ND-P / Si):

[0040] First, prepare MoS2 quantum dots: 0.08 g / mL Na2MoO4.2H2O and 0.1 g / mL cysteamine hydrochloride were mixed evenly in a volume ratio of 1:2, and the pH was adjusted to 6 with 0.15 mol / L HCl solution; then placed in a reactor, treated at 200°C for 36 hours, taken out, and the upper light yellow clear liquid was taken for later use;

[0041] At the same time, use a pipette to transfer 10 μL of dimethylaminotrimethylsilane and dissolve it in 50 mL of xylene solution, mix well and set aside;

[0042] Then, the prepared SiO2@Ag ND-P / Si composite substrate was immersed in a dimethylaminotrimethylsilane xylene mixture for 1 hour; then, the sample was immersed in the prepared MoS2 QDs sol to obtain a MoS2 QDs@SiO2@Ag ND-P / Si composite substrate, in which the dimethylaminotrimethylsilane is a silane coupling agent, which fixes the MoS2 QDs on the substrate surface;

[0043] e. Functionalization of MoS2 quantum dot-modified fluorescence enhancement substrate (MoS2 QDs@SiO2@Ag ND-P / Si):

[0044] The composite substrate (MoS2 QDs@SiO2@Ag ND-P / Si) was immersed in an aqueous solution of 0.1 mol / L mercaptoimidazole for functionalization to prepare a surface-modified substrate that can specifically detect Hg 2+ composite substrate.

[0045] The prepared MoS2 QDs@SiO2@Ag ND-P / Si substrate has good anti-reflection properties, and the presence of the silica shell can effectively prevent the non-radiative transition of the fluorescent material MoS2 QDs to the silver nanodendrites to cause quenching, making the composite structure have excellent fluorescence enhancement performance, with an enhancement factor of up to 12.4. This substrate has Hg 2+ The specific detection performance is 10 -12 mol / L.

[0046] Example 3

[0047] a. Preparation of silicon cone substrate (P / Si):

[0048] The silicon wafer was treated with acetone, chloroform, ethanol and deionized water in sequence under ultrasonic conditions for 5 minutes; then, the sample was placed in a 0.1 mol / L potassium hydroxide aqueous solution and reacted at 80°C for 30 minutes to obtain a silicon cone (P / Si) sample with light trapping ability; then, the sample was taken out, rinsed with deionized water, and blown dry for later use;

[0049] b. Preparation of fluorescence enhancement substrate (Au ND-P / Si):

[0050] Equal volumes of 0.06 mol / L hexadecyltrimethylammonium chloride and 0.5 mmol / L tetrachloroauric acid were mixed evenly, and 2% of the above volume of 0.08 mol / L ascorbic acid solution was added dropwise, and after stirring for 20 seconds, a silicon cone substrate (P / Si) was placed in the above mixed solution and allowed to stand at room temperature for 5 hours to deposit bionic flower-shaped gold nanoparticles Au ND, thereby obtaining a bionic fluorescence enhanced substrate Au ND-P / Si;

[0051] c. Preparation of fluorescence quenching-resistant substrate - polydopamine (PDA)-modified fluorescence enhancement substrate (PDA@Au ND-P / Si):

[0052] The Au ND-P / Si substrate was placed in a 50 mmol / L, pH=8.5 Tris-HCl buffer, and a 1 mg / mL dopamine aqueous solution was added. After reacting for 3 hours, the supernatant was removed, and then the substrate was cleaned and dried for later use to obtain an anti-fluorescence quenching PDA@Ag ND-P / Si substrate.

[0053] d. Preparation of ZnO quantum dot modified fluorescence enhancement substrate (ZnO QDs@PDA@Au ND-P / Si):

[0054] First, ZnO quantum dots were prepared: 20 mL of 0.4 mol / L LiOH·H2O was added to 40 mL of 0.2 mol / L ZnAc2·2H2O ethanol solution, and the mixture was stirred at 20°C for 20 min to obtain a ZnO quantum dot ethanol solution; then, 60 mL of the ZnO quantum dot ethanol solution was added to 120 mL of n-hexane to produce a white granular precipitate, which was allowed to stand for 2 h; finally, the mixture was centrifuged for 10 min (2000 r / min), the supernatant was removed, and 20 mL of anhydrous ethanol was added to dissolve the precipitate to obtain a clear and transparent ZnO sol;

[0055] At the same time, use a pipette to transfer 10 μL of 3-aminopropyltriethoxysilane and dissolve it in 50 mL of xylene solution, mix well and set aside;

[0056] Then, the prepared PDA@Au ND-P / Si composite substrate was immersed in a xylene mixture of 3-aminopropyltriethoxysilane for 1 hour; then, the sample was immersed in the prepared ZnO QDs sol to obtain a ZnO QDs@PDA@Au ND-P / Si composite substrate, in which 3-aminopropyltriethoxysilane can bond with the hydroxyl groups on the surface of PDA, and fix the ZnO QDs on the substrate surface through the coordination of the lone pair electrons of the amino group with the empty zinc orbital of the zinc oxide quantum dots;

[0057] e. Functionalization of ZnO quantum dot-modified fluorescence enhancement substrate (ZnO QDs@PDA@Au ND-P / Si):

[0058] The composite substrate (ZnO QDs@PDA@Au ND-P / Si) was immersed in an aqueous solution of 0.1 mol / L mercaptoimidazole for functionalization to prepare a surface that can specifically detect Hg 2+ composite substrate.

[0059] The prepared ZnO QDs@PDA@Au ND-P / Si substrate has good anti-reflection properties, and the presence of PDA can effectively prevent the non-radiative transition of the fluorescent substance ZnO QDs to the silver nanodendrites to cause quenching, making the composite structure have excellent fluorescence enhancement performance, and the enhancement factor is as high as 13.46. This substrate has Hg 2+ The specific detection performance is 10 -13 mol / L.

[0060] Example 4

[0061] a.Porous copper (Cu NPS ) Preparation of substrate:

[0062] A 1 cm2 piece of brass foil was rubbed with sandpaper and ultrasonically removed with deionized water, acetone and isopropyl alcohol to remove any surface oxides and organic contaminants. The cleaned brass foil was immersed in concentrated hydrochloric acid and heated to 70°C. This process explicitly removed zinc and any oxides from the surface. It was then rinsed thoroughly with deionized water and dried with compressed nitrogen.

[0063] b. Fluorescence enhancement substrate (Ag ND-Cu NPS ) Preparation:

[0064] Cu NPS The substrate was immersed in a 0.01 mol / L AgNO3 solution for 15 min. After the reaction, the residual silver nitrate solution was washed with ultrapure water.

[0065] c. Anti-fluorescence quenching substrate (SiO2@Ag ND-Cu NPS ) Preparation:

[0066] 40.0mL of ethanol, 15.0mL of ammonia water and 3.0mL of tetraethyl orthosilicate were reacted at a constant temperature for 20min; then, 0.3mL of ammonia water was added to the reaction solution and stirred for 2h to obtain SiO2 sol; then, 20μL of the prepared SiO2 sol was added dropwise onto the silver nano-dendritic structure, and finally, the sample was placed in a muffle furnace, the heating rate was controlled at 5℃ / min, the temperature was raised to 70℃, solidified for 1h, and then the temperature was raised to 150℃, and calcined at 150℃ for 1h to obtain SiO2@Ag ND-Cu NPS structure;

[0067] d. SnO2 quantum dots modified fluorescence enhancement substrate (SnO2 QDs@SiO2@Ag ND-Cu NPS ) Preparation:

[0068] 2.257g SnCl2·2H2O and 0.077g CH4N2S were dissolved in 50mL deionized water and magnetically stirred at room temperature for 24h to synthesize SnO2 quantum dots. SnCl2 was hydrolyzed and oxidized to convert into SnO2 quantum dots in the solution, and heated in a hydrothermal reactor at 180℃ for 5h to ensure that the SnO2 quantum dots were completely crystallized, and the supernatant was taken for later use;

[0069] Meanwhile, take 10 μL of 3-aminopropyltriethoxysilane and dissolve it in 50 mL of xylene solution, mix well and set aside;

[0070] Then, the prepared SiO2@Ag ND-Cu NPSThe composite substrate was immersed in a mixture of 3-aminopropyltriethoxysilane and xylene for 1 h; then, the sample was immersed in the prepared SnO2 QDs sol to obtain SnO2 QDs@SiO2@Ag ND-Cu NPS Composite base.

[0071] e. SnO2 quantum dots modified fluorescence enhancement substrate (SnO2 QDs@SiO2@Ag ND-Cu NPS ) functional processing:

[0072] The composite substrate (SnO2 QDs@SiO2@Ag ND-Cu NPS ) was immersed in a 0.1 mol / L aqueous solution of thioglycolic acid and functionalized to prepare a sample capable of specifically detecting Hg 2+ composite substrate.

[0073] Prepared SnO2 QDs@SiO2@Ag ND-Cu NPS The substrate has good anti-reflection properties, and the presence of the silica shell can effectively prevent the non-radiative transition of the fluorescent substance SnO2 QDs to the silver nanodendrites to cause quenching, making the composite structure have excellent fluorescence enhancement performance, with an enhancement factor of up to 13.4. This substrate has Hg 2+ The specific detection performance is 10 -12 mol / L.

[0074] Example 5

[0075] a. Preparation of silicon cone substrate (P / Si):

[0076] The single crystal silicon wafer was treated with acetone, chloroform, ethanol and deionized water in sequence under ultrasonic conditions for 10 minutes; then, the sample was placed in a 0.1 mol / L potassium hydroxide aqueous solution and reacted at 90°C for 20 minutes to obtain a silicon cone (P / Si) sample with light trapping ability; then, the sample was taken out, rinsed with deionized water, and blown dry for later use;

[0077] b. Preparation of PDMS substrate

[0078] Take 1.5g of PDMS prepolymer and 0.15g of curing agent (Sylgard TM 184silicone elastomercuring agent), stirred for 15 min, then cast it on the P / Si surface, and then heated in an oven at 80°C for 90 min to completely cure the PDMS, and finally peeled off from the P / Si surface to obtain the PDMS substrate; then the PDMS substrate was cleaned with O2 plasma for 10 s to make its surface hydrophilic;

[0079] c. Preparation of fluorescence enhancement substrate (Ag ND-PDMS):

[0080] First, the zinc plate was treated with hydrochloric acid (99.9%) to remove ZnO and other impurities, and then rinsed with distilled water. Then the zinc plate was immersed in 0.1M AgNO3 solution for 60s, rinsed with distilled water and ethanol several times, and then ultrasonicated in clean water. The solution was poured onto the PDMS substrate to obtain Ag ND-PDMS.

[0081] d. Preparation of anti-fluorescence quenching substrate-PMMA modified fluorescence enhancement substrate (PMMA@AgND-PDMS):

[0082] 10 mg of PMMA was dissolved in 50 mL of xylene solution. After mixing evenly, part of the solution was spin-coated on AgND-PDMS to obtain a PMMA@AgND-PDMS structure.

[0083] e. Preparation of CdS quantum dot modified fluorescence enhancement substrate (CdS QDs@PMMA@AgND-PDMS):

[0084] CdCl2·H2O (1.8812 g, 9.34 mmol) was dissolved in 100 mL of pure water and stirred, purged with nitrogen for 30 min, and then the pH of the solution was carefully adjusted to 6.5 by adding 1 M NaOH dropwise. Na2S·H2O (0.7296 g, 9.35 mmol) was dissolved in 5 mL of pure water, and then the Na2S solution was added to the reaction mixture under nitrogen, and after reflux at 65 ° C for 1 h, a bright yellow colloid was obtained;

[0085] At the same time, use a pipette to transfer 10 μL of dimethylaminotrimethylsilane and dissolve it in 50 mL of xylene solution. Mix well.

[0086] Then, the prepared PMMA@Ag ND-PDMS composite substrate was cleaned with O2 plasma for 10 seconds to make its surface hydrophilic, and then immersed in a mixture of dimethylaminotrimethylsilane and xylene for 1 hour; then, the sample was immersed in the prepared CdS QDs sol to obtain a CdS QDs@PMMA@AgND-PDMS composite substrate, in which dimethylaminotrimethylsilane is a silane coupling agent, which fixes CdS QDs on the surface of the substrate;

[0087] f. Functionalization of CdS quantum dot modified fluorescence enhancement substrate (CdS QDs@PMMA@AgND-PDMS):

[0088] The composite substrate (CdS QDs@PMMA@AgND-PDMS) was immersed in a 0.1 mol / L aqueous solution of thioglycolic acid for functionalization to prepare a substrate that can specifically detect Hg 2+ composite substrate.

[0089] The prepared CdS QDs@PMMA@AgND-PDMS substrate has good anti-reflection properties, and the presence of the PMMA layer can effectively prevent the non-radiative transition of the fluorescent substance CdS QDs to the silver nanodendrites to cause quenching, making the composite structure have excellent fluorescence enhancement performance, with an enhancement factor of up to 11.4. 2+ The specific detection performance is 10 -11 mol / L.

[0090] Example 6

[0091] a. Preparation of silicon cone substrate (P / Si):

[0092] The single crystal silicon wafer was treated with acetone, chloroform, ethanol and deionized water in sequence under ultrasonic conditions for 10 minutes; then, the sample was placed in a 0.1 mol / L potassium hydroxide aqueous solution and reacted at 90°C for 20 minutes to obtain a silicon cone (P / Si) sample with light trapping ability; then, the sample was taken out, rinsed with deionized water, and blown dry for later use;

[0093] b. Preparation of PDMS substrate

[0094] Take 1.5g of PDMS prepolymer and 0.15g of curing agent (Sylgard TM 184silicone elastomercuring agent), stirred for 15 min, then cast it on the P / Si surface, and then heated in an oven at 80°C for 90 min to completely cure the PDMS, and finally peeled off from the P / Si surface to obtain the PDMS substrate; then the PDMS substrate was cleaned with O2 plasma for 10 s to make its surface hydrophilic;

[0095] c. Preparation of fluorescence enhancement substrate (Ag ND-PDMS):

[0096] Using magnetron sputtering equipment, the vacuum degree was 8×10 -4 Pa, the sputtering power was 100 W, and the sputtering time was 50 s to form a 100 nm Cu film on the clean PDMS substrate surface;

[0097] The PDMS substrate with Cu on the surface was inserted into a 0.01 mol / L AgNO3 solution for 15 min. After the reaction was completed, the residual silver nitrate solution was washed with ultrapure water.

[0098] d. Preparation of fluorescence enhancement substrate (PDA@Ag ND-PDMS) modified with anti-fluorescence quenching substrate:

[0099] The Ag ND-PDMS substrate was placed in a 50 mmol / L, pH=8.5 Tris-HCl buffer, and a 1 mg / mL dopamine aqueous solution was added. After reacting for 3 hours, the supernatant was removed, and then the substrate was cleaned to obtain an anti-fluorescence quenching PDA@Ag ND-PDMS substrate.

[0100] d. Preparation of ZnO quantum dots modified fluorescence enhancement substrate (ZnO QDs@PDA@Ag ND-PDMS):

[0101] First, ZnO quantum dots were prepared by adding 20 mL of 0.4 mol / L LiOH·H2O to 40 mL of 0.2 mol / L ZnAc2·2H2O ethanol solution, stirring at 20°C for 20 min to obtain a ZnO quantum dot ethanol solution; then, 60 mL of the ZnO quantum dot ethanol solution was added to 120 mL of n-hexane to produce a white granular precipitate, which was allowed to settle for 2 h; finally, centrifuged for 10 min (2000 r / min), the supernatant was removed, and 20 mL of anhydrous ethanol was added to dissolve the precipitate to obtain a clear and transparent ZnO sol;

[0102] Then, the prepared PDA@Ag ND-PDMS composite substrate was immersed in the prepared ZnO QDs sol to obtain a ZnOQDs@PDA@Ag ND-PDMS composite substrate, and the amino groups in PDA coordinated with the zinc empty orbitals in the zinc oxide quantum dots to fix the ZnO QDs on the substrate surface;

[0103] e. Functionalization of ZnO quantum dot-modified fluorescence enhancement substrate (ZnO QDs@PDA@Ag ND-PDMS):

[0104] The composite substrate (ZnO QDs@PDA@Ag ND-PDMS) was immersed in an aqueous solution of 0.1 mol / L mercaptoimidazole for functionalization to prepare a substrate that can specifically detect Hg 2+ composite substrate.

[0105] The prepared ZnO QDs@PDA@Ag ND-PDMS substrate has good anti-reflection properties, and the presence of PDA can effectively prevent the non-radiative transition of the fluorescent substance ZnO QDs to the silver nanodendrites to cause quenching, making the composite structure have excellent fluorescence enhancement performance, with an enhancement factor of up to 13.6. 2+ The specific detection performance is 10 -13mol / L.

[0106] Example 7

[0107] a. Preparation of silicon cone substrate (P / Si):

[0108] The silicon wafer was treated with acetone, chloroform, ethanol and deionized water in sequence under ultrasonic conditions for 5 minutes; then, the sample was placed in a 0.1 mol / L sodium hydroxide aqueous solution and reacted at 80°C for 50 minutes to obtain a silicon cone (P / Si) sample with light trapping ability; then, the sample was taken out, rinsed with deionized water, and blown dry for later use;

[0109] b. Preparation of fluorescence enhancement substrate (Ag ND-P / Si):

[0110] The sample was placed in a mixed solution of silver nitrate (AgNO3) and hydrofluoric acid (HF) with concentrations of 0.01 mol / L and 1.8 mol / L respectively. After reacting for 11 minutes, silver nanocrystals Ag ND were deposited to obtain the bionic fluorescence enhancement substrate Ag ND-P / Si.

[0111] c. Preparation of anti-fluorescence quenching substrate - PMMA modified fluorescence enhancement substrate (PMMA@AgND-Ag ND-P / Si):

[0112] 10 mg of PMMA was dissolved in 50 mL of xylene solution, and after mixing evenly, part of the solution was spin-coated onto AgND-P / Si to obtain a PMMA@Ag ND-P / Si structure.

[0113] d. Preparation of CdS quantum dot modified fluorescence enhancement substrate (CdS QDs@PMMA@Ag ND-P / Si):

[0114] CdCl2·H2O (1.8812 g, 9.34 mmol) was dissolved in 100 mL of pure water and stirred, purged with nitrogen for 30 min, and then the pH of the solution was carefully adjusted to 6.5 by adding 1 M NaOH dropwise. Na2S·H2O (0.7296 g, 9.35 mmol) was dissolved in 5 mL of pure water. The Na2S solution was then added to the reaction mixture under nitrogen. After reflux at 65 °C for 1 h, a bright yellow colloid was obtained;

[0115] At the same time, use a pipette to transfer 10 μL of dimethylaminotrimethylsilane and dissolve it in 50 mL of xylene solution. Mix well.

[0116] Then, the prepared PMMA@Ag ND-P / Si composite substrate was cleaned with O2 plasma for 10 seconds to make its surface hydrophilic, and then immersed in a mixture of dimethylaminotrimethylsilane and xylene for 1 hour; subsequently, the sample was immersed in the prepared CdS QDs sol to obtain a CdS QDs@PMMA@Ag ND-P / Si composite substrate, in which the dimethylaminotrimethylsilane is a silane coupling agent, which fixes the CdS QDs on the substrate surface.

[0117] f. Functionalization of CdS quantum dot modified fluorescence enhancement substrate (CdS QDs@PMMA@Ag ND-P / Si):

[0118] The composite substrate (CdS QDs@PMMA@Ag ND-P / Si) was immersed in a 0.1 mol / L cysteine ​​solution and functionalized to prepare a substrate that can specifically detect Hg 2+ composite substrate.

[0119] The prepared CdS QDs@PMMA@Ag ND-P / Si substrate has good anti-reflection properties, and the presence of the PMMA layer can effectively prevent the non-radiative transition of the fluorescent substance CdS QDs to the silver nanodendrites to cause quenching, making the composite structure have excellent fluorescence enhancement performance, with an enhancement factor of up to 12.1. 2+ The specific detection performance is 10 -12 mol / L.

[0120] Example 8

[0121] a. Preparation of anodized aluminum oxide (AAO) substrate:

[0122] A two-step anodization method was used to prepare AAO substrates with high regularity. First, commercially available aluminum foil (99.99%) was electrochemically polished in a mixture of ethanol and perchloric acid (volume ratio 7:1), 20 V was applied to a graphite counter electrode for 4 min, and then the polished aluminum was anodized on a graphite counter electrode at 40 V in a 0.3 M oxalic acid aqueous solution for 10 h. The thick aluminum oxide layer formed by the first anodization was completely etched in an aqueous solution of chromic acid and phosphoric acid to leave a regularly ordered array of nano-indentations on the aluminum surface.

[0123] b. Preparation of fluorescence enhanced substrate (Au ND-AAO):

[0124] Equal volumes of 0.06 mol / L hexadecyltrimethylammonium chloride and 0.5 mmol / L tetrachloroauric acid were mixed evenly, and 2% of the above volume of 0.08 mol / L ascorbic acid solution was added dropwise. After stirring for 20 seconds, the AAO substrate was placed in the above mixed solution and allowed to stand at room temperature for 5 hours to deposit bionic flower-shaped gold nanoparticles Au ND, thereby obtaining the bionic fluorescence enhanced substrate Au ND-AAO.

[0125] c. Preparation of anti-fluorescence quenching substrate (SiO2@Au ND-AAO):

[0126] 40.0mL of ethanol, 15.0mL of ammonia water and 3.0mL of tetraethyl orthosilicate were reacted at a constant temperature for 20min; then, 0.3mL of ammonia water was added to the above reaction solution, and the reaction was stirred for 2h to obtain SiO2 sol; then, 20uL of the above prepared SiO2 sol was added dropwise to the silver nano-dendritic structure, and finally, the sample was placed in a muffle furnace, the heating rate was controlled at 5℃ / min, the temperature was raised to 70℃, solidified for 1h, and then the temperature was raised to 150℃, and calcined at 150℃ for 1h to obtain SiO2@Au ND-AAO structure;

[0127] d. Preparation of MoS2 quantum dot modified fluorescence enhancement substrate (MoS2 QDs@SiO2@Au ND-AAO):

[0128] First, prepare MoS2 quantum dots. Mix 0.08g / mL Na2MoO4.2H2O and 0.1g / mL cysteamine hydrochloride in a volume ratio of 1:2, adjust the pH to 6 with 0.15mol / L HCl solution; then place in a reactor, treat at 200℃ for 36h, take out, and take the upper light yellow clear liquid for later use;

[0129] At the same time, use a pipette to transfer 10 μL of dimethylaminotrimethylsilane and dissolve it in 50 mL of xylene solution. Mix well.

[0130] Then, the prepared SiO2@Au ND-AAO composite substrate was immersed in a dimethylaminotrimethylsilane xylene mixture for 1 hour; then, the sample was immersed in the prepared MoS2 QDs sol to obtain a MoS2 QDs@SiO2@Au ND-AAO composite substrate, in which the dimethylaminotrimethylsilane is a silane coupling agent, which fixes the MoS2 QDs on the substrate surface;

[0131] e. Functionalization of MoS2 quantum dot-modified fluorescence enhancement substrate (MoS2 QDs@SiO2@Au ND-AAO):

[0132] The composite substrate (MoS2 QDs@SiO2@Au ND-AAO) was immersed in a 0.1 mol / L aqueous solution of mercaptopropionic acid for functionalization to prepare a surface-modified substrate that can specifically detect Hg 2+ composite substrate.

[0133] The prepared MoS2 QDs@SiO2@Au ND-AAO substrate has good anti-reflection properties, and the presence of the silica shell can effectively prevent the non-radiative transition of the fluorescent material MoS2 QDs to the silver nanodendrites to cause quenching, making the composite structure have excellent fluorescence enhancement performance, with an enhancement factor of up to 13.3. 2+ The specific detection performance is 10 -13 mol / L.

[0134] The embodiments provided above are not intended to limit the scope of the present invention, and the steps described are not intended to limit the execution order thereof. Those skilled in the art may make obvious improvements to the present invention in combination with existing common knowledge, which also fall within the scope of protection defined by the claims of the present invention.

Claims

1. A bionic fluorescence enhancement substrate for mercury ion sensing detection, characterized in that: include: substrate; Noble metal particles located on the surface of the substrate; An anti-fluorescence quenching protective layer located on the noble metal particles; Wherein, the substrate, the noble metal particles and the anti-fluorescence quenching protective layer have a fluorescence enhancement effect; A specific mercury ion sensing detection layer located on the surface of the anti-fluorescence quenching protection layer; Wherein, the specific mercury ion sensing detection layer comprises: Fluorescent quantum dots; A mercury ion-specific recognition layer is bonded to the surface of fluorescent quantum dots.

2. The bionic fluorescence enhanced substrate for mercury ion sensing detection according to claim 1, characterized in that: The substrate is one or more of single crystal silicon, polycrystalline silicon, quartz, glass, fluorine-doped tin dioxide conductive glass, indium tin oxide conductive glass, carbon cloth, paper, cellulose film, stainless steel, metal nickel, metal copper, metal titanium, titanium oxide, metal aluminum, aluminum oxide, indium phosphide, silicon carbide, silicon nitride, diamond, sapphire, gallium arsenide, polydimethylsiloxane, polyethylene terephthalate, polymethyl methacrylate, polyethylene, and polyvinylidene fluoride.

3. The bionic fluorescence enhancement substrate for mercury ion sensing detection according to claim 1, characterized in that: The substrate surface has a light trapping structure, which is one or more of a pyramid shape, a column shape, a rod shape, a tube shape, a nanowire shape, an inverted pyramid shape, a nanosheet shape, a bowl shape, and a porous shape.

4. The bionic fluorescence enhancement substrate for mercury ion sensing detection according to claim 1, characterized in that: The precious metal particles are one or more of silver, gold, copper, platinum and alloys thereof.

5. The bionic fluorescence enhancement substrate for mercury ion sensing detection according to claim 1, characterized in that: The micro-nano morphology of the precious metal particles has one of the following shapes: bionic tree branch shape, bionic flower shape, and bionic sea urchin shape.

6. The bionic fluorescence enhancement substrate for mercury ion sensing detection according to claim 1, characterized in that: The anti-fluorescence quenching protective layer is a non-conductive film, including one or more of aluminum oxide, SiO2, PMMA, polyvinyl acetate polymers, polyacrylamide polymers, polyethylene glycol, polyallylamine, polystyrene polymers, polyether polymers, polyvinyl alcohol, polydopamine, polysiloxane, polyurethane, glass, zirconium oxide, hydroxyapatite, and aluminosilicate.

7. The bionic fluorescence enhancement substrate for mercury ion sensing detection according to claim 1, characterized in that: The siloxane molecules are modified on the anti-fluorescence quenching protective layer to facilitate the assembly of the specific mercury ion sensing detection layer. The siloxane molecules must contain one or more functional groups selected from the group consisting of amino, carboxyl, and pyridine groups, and may be selected from the group consisting of 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, dimethylaminotrimethylsilane, 3-carboxypropyltrimethoxysilane, 4-anilinotriethoxysilane, and N-(3-trimethoxysilylpropyl)pyrrole.

8. The bionic fluorescence enhancement substrate for mercury ion sensing detection according to claim 1, characterized in that: The fluorescent quantum dots in the specific mercury ion sensing detection layer are one or more of ZnO quantum dots, MgO quantum dots, CuO quantum dots, g-C3N4 quantum dots, CdS quantum dots, SnO2 quantum dots, MoS2 quantum dots, zinc sulfide quantum dots, zinc selenide quantum dots, cadmium selenide quantum dots, lead sulfide quantum dots, lead selenide quantum dots, graphene quantum dots, and carbon quantum dots.

9. The bionic fluorescence enhancement substrate for mercury ion sensing detection according to claim 1, characterized in that: The molecules constituting the mercury ion specific recognition layer contain two functional groups, thiol and amino, including but not limited to one or more of mercaptoimidazole, thioglycolic acid, mercaptopropionic acid, amino acid molecules, triethanolamine, glutathione, mercaptosuccinic acid, and cysteine.

10. The method for preparing a bionic fluorescence enhanced substrate for mercury ion sensing detection according to claim 1, characterized in that: include: Constructing the substrate; Precious metal particles are deposited on the surface of the substrate, and the deposition technology of the precious metal particles includes one or more of chemical deposition technology, electrodeposition technology, electrical replacement reaction technology, and photoreduction technology; Assembling an anti-fluorescence quenching protective layer on the noble metal particles; Preparation of fluorescent quantum dots; The surface of the anti-fluorescence quenching protective layer is modified so that it can be assembled with fluorescent quantum dots; The surface functionalization of fluorescent quantum dots enables them to specifically sense, identify and detect mercury ions.